AL-MIHNAH DALAM DINASTY ABBASIYYAH KHALIFAH AL-MA’MUN: Mihna in The Reign of Al-Ma’mun by Iskandar Arnel - Ahmad Lahmi (Saintifika Islamica, 2015)
The al-Mihna is one of the fitan in Islamic history which shows a confrontation between the ruling and orthodok Sunni ‘ulama in the ‘Abbasid dynasty. Even though al-Mihna is religious in nature, it has a political significant in the sense that the Mihna is employed by al-Ma’mun to control the influence of the ‘ulama in the society, to establish a new orthodok called al-Mu’tazilla as state religious doctrine, and to get supports from the Shi’ites.